PEMETAAN RUTE WISATA RELIGI KABUPATEN SUMENEP - Deshariyanto, Dwi; Fansuri, Subaidillah; Diana, Anita Intan Nura (Fakultas Teknik, Universitas Wiraraja, 2024)
Religious tourism especially in the mainland Sumenep district consists of Jami‘ Mosque, Asta Tinggi, Asta Jokotole, Asta Katandur, Asta Gumo’, Asta Yusuf, Asta K. Faqih and Asta Buju' Panaongan. Mapping of religious tourism has not been mapped in detail especially the route, distance and travel time from the city centre to the location of religious tourism in the Sumenep district. The purpose of this study is to determine the route, calculate the distance and travel time of religious tourism from the city centre to religious tourism and between religious tourism in the Sumenep district. The nearest religious tourism from the city centre is Jami‘ Mosque by 650 meters and the farthest religious tourism distance from the city centre is Asta Buju’ Panaongan by 31,100 meters, while the fastest travel time from the city centre is Jami‘ Mosque by 3 minutes and the longest travel time from the city centre is Asta Buju’ Panaongan by 44 minutes. The closest path between religious tourism Jami‘ Mosque to Asta high with a distance of 2,700 metres and the furthest religious tourism path between religious tourism Asta Yusuf to Asta Buju’ Panaongan with a distance of 43,825 metres. The fastest travel time from Jami‘ Mosque to Asta tinggi is 8 minutes and the longest travel time from Asta Yusuf to Asta Buju’ Panaongan with a travel time of 77 minutes.